2007
DOI: 10.1101/gad.1524107
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic disruption of Polycomb-repressive complex 2-mediated gene repression selectively induces apoptosis in cancer cells

Abstract: [Keywords: EZH2; PRC2; apoptosis; breast cancer; histone methylation] Supplemental material is available at http://www.genesdev.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

70
819
3
4

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 823 publications
(906 citation statements)
references
References 64 publications
70
819
3
4
Order By: Relevance
“…Importantly, both treatments resulted in a marked decrease in global levels of H3K27me3 (Figure 6b), as previously reported, 25,40,41 whereas the levels of H3K9me3, another repressive mark, remained unchanged demonstrating that they act mainly through inhibition of EZH2-containing complexes at the used doses on the basis of previous reports for DZNep. 24,40,[42][43][44][45] Consistently with EZH2 silencingdependent effects, the appearance of apoptotic Annexin V-positive cells was seen in both DZNep-and MC1945-treated RH30 cells ( Figure 6c) associated with transcriptional upregulation of FBXO32 gene and decreased Myogenin levels after 72 h (Figure 6d). Collectively, these observations indicate that pharmacological approaches either favoring the degradation or blocking the catalytic functions of EZH2 affect the proliferative potential of PAX3-FOXO1-positive alveolar RMS cells and mirror the effect of siRNA-and short hairpin RNAmediated EZH2 depletion in derepressing FBXO32.…”
Section: Fbxo32 Is Directly Targeted By Ezh2 In Pax3-foxo1 Alveolar Rsupporting
confidence: 89%
See 3 more Smart Citations
“…Importantly, both treatments resulted in a marked decrease in global levels of H3K27me3 (Figure 6b), as previously reported, 25,40,41 whereas the levels of H3K9me3, another repressive mark, remained unchanged demonstrating that they act mainly through inhibition of EZH2-containing complexes at the used doses on the basis of previous reports for DZNep. 24,40,[42][43][44][45] Consistently with EZH2 silencingdependent effects, the appearance of apoptotic Annexin V-positive cells was seen in both DZNep-and MC1945-treated RH30 cells ( Figure 6c) associated with transcriptional upregulation of FBXO32 gene and decreased Myogenin levels after 72 h (Figure 6d). Collectively, these observations indicate that pharmacological approaches either favoring the degradation or blocking the catalytic functions of EZH2 affect the proliferative potential of PAX3-FOXO1-positive alveolar RMS cells and mirror the effect of siRNA-and short hairpin RNAmediated EZH2 depletion in derepressing FBXO32.…”
Section: Fbxo32 Is Directly Targeted By Ezh2 In Pax3-foxo1 Alveolar Rsupporting
confidence: 89%
“…We then provide evidence that this phenomenon is due, at least in part, to the derepression of the tumor suppressor gene FBXO32, already shown to be induced by EZH2 knockdown in cells of solid and blood EZH2 supports PAX3-FOXO1 rhabdomyosarcoma survival R Ciarapica et al cancers. 23,28,40 Indeed, the simultaneous depletion of FBXO32 and EZH2 greatly reduced the apoptotic cell response, suggesting that EZH2 protects fusion-positive alveolar RMS cells from apoptosis in part by repressing FBXO32. Of note, FBXO32 derepression is associated with both a reduction in EZH2 recruitment and a decrease in H3K27me3 mark to the FBXO32 gene promoter, indicating that in our cell context EZH2 is recruited at this promoter and is enzymatically active to repress transcription, as already shown.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…40 Tan et al identified 3-deazaneplanocin A (DZNep), which is a small molecule that inhibits the expression of PRC2 complex proteins containing EZH2 and induces apoptotic cell death together with histone deacetylase (HDAC) inhibitors in cancer cells, but not in normal cells. 41 Taken together with high expression of EZH2 in NSCLC cells and its association with aggressive phenotypes, PRC2 inhibitors like DZNep, which, together with HDAC inhibitor, pharmacologically reverses cancer-associated epigenetic gene repression, may provide potent therapy for NSCLC.…”
Section: Bmi1 and Ezh2 Expression In Nsclc/kikuchi Et Almentioning
confidence: 99%